THE ABILITY OF ANTI-INFLAMMATORY JATROPHA CURCAS LEAF EXTRACT AT COX-2 EXPRESSION ON MONOCYTES WERE EXPOSED LPS - Astuti Pudji (UNEJ e-Proceeding)
Leukocyte is the main responsible cell in theimmunity sistem which move freely in thecirculation. Macrophag, neutrophil, dendrytic cell,mast cell, eosinophil, basophil and natural killer (NKcell) are important part of adaptive immunity.Macrophag is monocyte that leaves the circulationand move into the tissue to identify and directly killthe cause of the infection. Its killing mechanism isthrough the phagocytosis which responded to thepathogen bacteria, so the monocyte viabilty isimportant factor of the immune response.1The interest of alternative medicine use in healththerapy has been increased in the past few years.2Many researches has been conducted to discoverthe phytochemical of many herbs around the world,one of them is Jatropha curcas. Its leaves and branchcontain flavonoid, apigenin, vitexin, dan isovitexin. Italso contain dimer of triterpene alcohol (C63H117O9)and two glycoside flavonoid.3 In Indonesia, theJatropha leaves has been used to cure the cough, asantiseptic, antipyretic, bloating relief,antihelminthics, gingivitis, stimulate hair-growth,anti-dandruff, antimalarial, and destruct the kidneystone.4 Flavonoid has been known for its antimicrobaand anti-viral activity. Triterpenoid also hasthe same activity and has been frequently found inherbs. It also helps the skin repair.5 The extract ofJatropha leaves contain the flavonoid as theantiinflammatory agent.In the previous study6, the treatment with Jatrophaleaves extract decreased the peripheral lymphocytesof Escherichia coli (E.coli)-induced male mice.Treatment with 5% concentration of Jatropha leavesextract shows the better effect compared to 10%when given on 1st until 7th day. Maghfirotin 7 statedthe 10% concentration of Jatropha leaves extractalso suppress the elevation of peripheral neutrophilin E.coli-induced male mice.E.coli produce the well-know endotoxin,lypopolisacharide (LPS). Endotoxin has variespotention depend on the microorganisms, but itseffect is quite the same.8 LPS stimulates the immunecell through in vitro or in vivo environment, and hasimportant clinical relevation because it is directlyinvolved in Gram-negative bacteria mediatedinfection.9Based on the introduction, the Jatropha leavesextract mechanism towards the COX-2 expression,the enzyme which responsible in inflammationphase, yet still unknown. This study is to determinethe antiinflammatory activity of Jatropha leavesextract toward the COX-2 expression by using E. Colito induce the inflammation.MATERIALS AND METHODThis in-vitro study use the posttest only with controlgroup design. The independent variable is Jatrophaleaves extract in 5%, 10% and 15 % concentration.The dependent variable is COX-2 expression onmonocyte. The control variabel are monocytes typeand concentration, LPS from E.coli and researchprocedures.COX-2 expression was analyzed byimmunohistochemical method. Monocyte isolationwas incubated in Jatropha leaves extract and then itwas exposed to LPS from E.coli. The cell was washedand then the immunostaining was performed usethe antihuman COX-2 monoclonal antibody (Mab).The monocytes which expressed the COX-2 wasobserved and counted.